Studies on Selected Metals and other Pollutants in Urban Atmosphere in Dhaka Bangladesh - Rahman, Mohammad Arifur; Rahim, Abdur; Siddique, Nur-E-Alam; Alam, AM Shafiqul (Dhaka University Journal of Science, 2013)
The concentration of lead, iron and potassium were determined in suspended particulates matters (SPM) in the atmosphere Dhaka, Bangladesh between January and June, 2008. The sampling areas are Khandakar Mukarram Hossain Biggan Bhaban, University of Dhaka, Tejgaon, Hazaribagh, Uttara and Agargaon new colony. The average concentrations of TSP, PM10 and PM2.5 were 68, 43 and 35 ?g m-3, respectively. About 82% particles were from fine fraction (PM2.5) and 18% were from coarse fraction (PM10-2.5), which indicates mechanical processes are one of the main sources for the particulate matters in air of Dhaka. The concentration of lead, iron and potassium were determined by using atomic absorption spectrophotometer (AAS) for the size fraction of PM10 with highest concentrations recorded for iron (10.8 ?g/m3) and lowest for lead (0.10 ?g/m3). The average concentration of NOx, O3 and SOx with eight hours sampling were 82.8, 22.5 and 25.5 ?g/m3 respectively. This study revealed that the concentrations of Pb, K, Fe, CO, NOx, O3 and SOx in Dhaka City were higher than the WHO (World Health Organization) guideline values. Dhaka Univ. J. Sci. 61(1): 41-46, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15094